Workplace skills: a study of the skills taught in UiTMCS and its relevance to the construction industry in Sarawak / Foo Kien Kheng, Nagarajah Lee and Rudy Tawie - Foo, Kien Kheng; Lee, Nagarajah; Tawie, Rudy (2003)
The purpose of the study is to identify the skills taught to the DCE graduates and just to expose them to a predetermined set of skills which had been benchmarked earlier to make a comparison. It also seeks to explore the level of workplace knowledge and competency of both the DCE students as well as the graduates who are currently employed in the construction industry. This study also has practical considerations whereby the various parties concerned could use the findings to aid their decision making process. As this study has no intention of inferring the findings to the general population, the snowballing technique was employed to select the respondents which comprised the Part 6 DCE students, the lecturers who taught them, graduates of the same program and their supervisors.